2008
DOI: 10.1016/j.jadohealth.2007.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Sexual Risk Behaviors Among Newly Homeless Youth: A Longitudinal Study

Abstract: Living with nonfamily members and drug use appear to be the most salient in explaining sexual risk among newly homeless youth. Our findings indicate that interventions aimed at reducing sexual risk behaviors, and thereby reducing sexually transmitted diseases and HIV among newly homeless youth, need to help youth in finding housing associated with supervision and social support (family and institutional settings) as well as aim to reduce drug use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
65
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 20 publications
5
65
2
Order By: Relevance
“…5 Although other studies have reported an association between illicit drug use and risky sexual activity, 25 our study did not determine this association, perhaps due to its small sample size. However, we did find a nonsignificant trend toward increased risk of unprotected sex for those who used alcohol to intoxication.…”
contrasting
confidence: 55%
“…5 Although other studies have reported an association between illicit drug use and risky sexual activity, 25 our study did not determine this association, perhaps due to its small sample size. However, we did find a nonsignificant trend toward increased risk of unprotected sex for those who used alcohol to intoxication.…”
contrasting
confidence: 55%
“…As a result, these groups more frequently report sexual abuse, violence, discrimination, drug and alcohol use, and exchange of sex for money and favors. 6,9,14,21,22,26 Among homosexuals, homophobia has been identifi ed as the main factor driving them onto streets. 4.19 A qualitative study conducted in Los Angeles 21 showed that women's choice to use condoms is strongly affected by their emotional involvement and trust in their partner, and that sex occur due to various reasons including sexual abuse and need for affective involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Of Massachusetts high school students, 69% of homeless youth report current sexual activity [7]. Among recently homeless youth, half of females are sexually active at initial contact, and the rate of sexual activity increases over time [8].…”
mentioning
confidence: 99%
“…Among high school students in the United States, 12% of females have four or more lifetime sex partners [6]. Recently, homeless females average one sexual partner in the previous 3 months [8]. Among runaways, first sexual partners are about 3 years older.…”
mentioning
confidence: 99%
See 1 more Smart Citation